Psychological Problems and Needs of Deaf Adolescents: A Phenomenological Research - AYDOĞDU, BİLGE NURAN; YÜKSEL, MÜGE (ANI PUBLISHING, 2019)
Deaf individuals experience a significant number of problems because of language barrier. This study aims to discover the psychological problems and needs of deaf individuals in various problem areas. The study is designed as an interpretative phenomenological research. The study group consists of 17 participants from a special education vocational school for the deaf. MaxQDA-12 program was used in analysis. During this stage, all the codes were merged into themes just after the codification. As a result of this analysis phase, five main themes were created: individual life, deaf culture, family life, social life and education life. This study reached some findings about the psychological problems and needs of the deaf individuals in different environments. Findings indicate that the psychological problems and needs stem from communication problems, not from being a deaf. It has been seen that these communication problems restrict living spaces of deaf individuals and pose a threat to their mental health.
Keywords: Deaf; deaf adolescents; psychological problems; OF-HEARING CHILDREN; COMMUNICATION; CULTURE